Hepatitis B Markers in Tissue Donors. National Multicenter Study. Preliminary Results. (July 2018) - Ibáñez, Jacinto Sánchez; Serrat, Ana Vilarrodona; Aierbe, Clara Rodriguez; Montoro, Rafael Villalba; Calvo, Javier; Lopez, Elena Vuelta; Lorenzo, Maria Jose Martinez; Infiesta, Alvaro Meana; Romero, Manuel Gonzalez; Paneque, Sergio Fernandez
Abstract : Introduction: In tissue donors it is mandatory to perform screening for hepatitis B virus. Traditionally, when core antibody (HBcAb) is positive with hepatitis B surface antibody (HBsAb) positive, the donor is considered suitable. However, the literature contains isolated DNA positives cases with this profile. Methodology: We collected prospectively data for all tissue donors in Spain (except living donors) during 2017: age, type of donor (organ and tissue donor or tissue donor alone), cause of death, tissues procured and the hepatitis B markers. The incident of HBcAb, HBsAb and DNA was analyzed. We present the preliminary results for the first 9 months. During the congress we will present the data for the whole year. Results: In this period data from 1286 tissue donors were collected. 841 were male (65.4%). Mean age 63.5±15.1 years old. 824 (64.1%) were only tissue donors. Donors with tumor were 321 cases (25%). The most frequent tissue retrieved was ocular in 1247 cases (97%). In 536 cases (41.7%) the blood sample was obtained before cardiac arrest. In the case of only tissue donors the mean time from cardiac arrest till the blood was obtained was 180 minutes. The mean time from blood collection till centrifugation or sending to the lab was 193 minutes. HBsAg was positive in three cases (0.2%). HBcAb was positive in 118 cases (9.2%), in which HBsAb was negative in 23 cases (19.5%) and positive in 95 cases (85%). In 35 cases (36.5%) the titer of HBsAb was less than 100. We found 18 cases of DNA positive (1.4% of total cases, 1.8% of cases where DNA testing was performed, of which 1 was an organ and tissue donor); 2 of them (0.3%) with HBcAb and HBsAb negative (1 HBs Ag positive); 4 cases (5%)with HBcAb negative and HBsAb positive (1 case titer less than 100, 3 cases more than 100); 4 cases (19%) with HBcAb positive and HBsAb negative (1 HBsAg positive) and 8 cases (8.4%) with HBcAb and HBsAb positive (5 cases titer less than 100, 3 cases more than 100). In the logistic regression models HBcAb positive is associated with older donors (p=0.017) and only tissue donors (p=0.049). Conclusions: The frequency of HBcAb in tissue donors is very similar to that of organ donors in our country. The most risky profile to find DNA is HBcAb positive and HBsAb negative. The classic concept that with HBsAb positive the donor can be accepted has to be avoided. It seems clear that DNA testing must be mandatory, at least with HBcAb positive. Another concern is if it is necessary to do HBsAb and if so, what level of HBsAb can be considered acceptable, and how to proceed with those donors. Each Tissue Establishment should have a clear protocol regarding hepatitis B screening.